(untitled) (Canadian Dermatology Today, 2020)
During my residency training, we were taught to encourage parents to use Benadryl® (diphenhydramine) or Atarax®(hydroxyzine) at night to help their itchy children sleep better. Parents were instructed to use higher doses than labelling on the bottle suggested, as the clinical intent was to use it for its sedating side effects rather than any sort of specific treatment for their child’s atopic dermatitis. This past year, the Canadian Society for Allergy and Clinical Immunology (CSACI) came out with a position statement on proper antihistamine use, directly in opposition to this practice. First generation H1 antihistamines have side effects like sedation and impairment with decreased cognitive function. Although they may help initiate sleep, they have been shown to cause poor sleep quality. These antihistamines cross the blood brain barrier and cause significant CNS suppression. Some studies have shown a decrease in school performance in patients regularly taking this medication. Previous use of first generation antihistamines has a possible association with increased ADHD symptoms in children with atopic dermatitis.